1989
DOI: 10.1007/bf00134994
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on transport of hydrophobic particles and gas bubbles in porous media

Abstract: Adhesion of hydrophobic colloids (clay minerals) on the surface of bubbles of air and the transport of the composite units formed by bubbles and mineral particles were observed in a glass micro model.When a clay mineral suspension flowed in a porous medium that contained bubbles of air trapped in small pores, particles accumulated preferentially on the upstream portion of the bubbles, and quasi-stable bubble-mineral particle units were formed. With an increase in the flow velocity, the particles moved along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…From this point of view one might conclude that the montmorillonite particles tend to be negatively adsorbed while the kaolinite particles tend to positively adsorb. This is consistent with a study of adhesion of small particles to large air bubbles in suspensions by Goldenberg et al (18). They found that in dilute electrolyte solutions clays of low cation exchange capacity (kaolinite) adhered to bubble surfaces and formed surface structures.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…From this point of view one might conclude that the montmorillonite particles tend to be negatively adsorbed while the kaolinite particles tend to positively adsorb. This is consistent with a study of adhesion of small particles to large air bubbles in suspensions by Goldenberg et al (18). They found that in dilute electrolyte solutions clays of low cation exchange capacity (kaolinite) adhered to bubble surfaces and formed surface structures.…”
Section: Resultssupporting
confidence: 91%
“…Menon et al (12)(13)(14)(15)(16)(17) have published several accounts of their investigations of emulsions stabilized by finely divided solids; these papers provide convincing evidence that such solids can have important effects on interfacial tensions. Finally, we note that Goldenberg et al (18) have reported on the effects of suspended clays on transport in porous media containing gas bubbles.…”
Section: Introductionmentioning
confidence: 60%
“…For instance, enrichment of colloid-associated heavy metals and organic compounds at the surface of oceans and lakes have been reported (1)(2)(3)(4). Clays, humic acids, and microorganisms have also been found preferentially sorbed at air-water interfaces in unsaturated soils (5)(6)(7)(8)(9). Colloid partitioning at gas-water interfaces has been analyzed as a special case of heterocoagulation, the interaction between double-layers of dissimilar surfaces (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Colloid deposition kinetics in natural and model porous media have been studied as a function of colloid size, colloid type, surface properties, flow velocity, water content, pore size, and solution chemistry (Goldenberg et al, 1989; Elimelech and O'Melia, 1990a, 1990b; McDowell‐Boyer, 1992; Wan and Tokunaga, 1997; James and Chrysikopoulos, 2000; Gamerdinger and Kaplan, 2001; Lenhart and Saiers, 2002). Although great advancements have been made in the study of colloid reaction and transport in porous media, both theoretically and experimentally, our understanding of colloid–soil interactions and our ability to predict transport of colloids in natural subsurface media are limited.…”
mentioning
confidence: 99%